Cardiovascular risk stratification in stable coronary artery disease based on prognostic scores and models - S. N. Tolpygina; S Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
According to modern clinical guidelines, the strategy of examination and treatment of a patient with stable coronary artery disease depends on the prognosis. Despite the great number of prognostic models and scores, there is currently no unified approach for cardiovascular risk stratification. The article provides a literature review of the main current prognostic models and scores, taking into account their effectiveness and limitations.